The Evolving Journey of Green Hydrogen in India’s Progress Towards Net-Zero Carbon Emissions - Laud, Shivprasad (Global journal of Business and Integral Security, 2026)
“Green Hydrogen” (GH2) is becoming one of the main pillars of the Government’s goal of becoming Energy independent by 2047 and achieving Net-Zero Carbon Emissions in India by 2070. Towards this in 2023, “National Green Hydrogen Mission” (NGHM) was initiated with the target of producing 5 million metric tonnes a year by 2030. This initiative is supported by substantial Government funding to help reduce the reliance on hard-to-abate industries (such as steel, cement, and transport) and fossil fuels. As noted in this work, despite the strategic guidance presented by Policy frameworks and incentives, what is limiting faster progress are implementation gaps, regulatory ambiguity, and infrastructure limitations. Central to industry preparedness is technological innovation, financial stability, and trained manpower. With effective financial instruments like Green bonds, the risks of investment can be mitigated. Challenges include the high cost of capital, land acquisition, physical disintegration, insufficient R&D, enforced Policy implementation, increased financial infrastructure, employee training, scalable storage, and a high level of safety, among others.